Implementation Of Digital Islamic (Digislamic) To Improve Process Standards at SMA Al Muslim Tambun Bekasi - Damayanti, Khoirunnisa; Suharyat, Yayat; Aprilliantoni (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Digital Islamic is a platform owned by the Al Muslim Foundation that utilizes integrated technology to help various educational processes, one of which is the learning process. This study aims to determine the implementation of Digislamic in the learning process at SMA Al Muslim Tambun in terms of George C. Edwards III's theory with four indicators, namely communication, resources, disposition and bureaucratic structure; and knowing the achievement of process standards after implementing Digislamic. This study used a descriptive qualitative approach. The results showed that communication was conveyed well, clearly and consistently; resources consist of adequate staff and have expertise in accordance with their duties and authorities, facility resources provided electronic devices, accounts, and the internet; the disposition of the foundation as a positive, firm, open, responsible and solutive leader and the management of the SMA unit as an implementer provide positive support; The bureaucratic structure applied is a top down structural approach and has complete and clear SOPs. The use of Digislamic provided a significant change in the standard of process at Al Muslim High School.